Thermosetting polyarylether resin as well as prepreg and halogen-free flame-retardant high-frequency high-speed copper-clad plate prepared from thermosetting polyarylether resin
By introducing unsaturated hydrocarbons containing heteroatoms into the polyarylene resin and using a continuous flow microchannel reactor, a thermoset polyarylene resin with excellent dielectric properties and low cost is prepared, and the existing thermosetting type is solved. The problems of insufficient dielectric performance and high production cost of copper clad plates have achieved the production of halogen-free flame-retardant high-frequency high-speed copper clad plates, meeting the requirements of high-frequency and high-speed communication and environmental protection laws.
Patent Information
- Application Number
- CN202411768385.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
AI Technical Summary
The existing thermoset copper clad plate has high dielectric constant and dielectric loss, which limits its use at low frequencies and cannot meet the performance requirements in the field of high-frequency and high-speed communications. In addition, it is difficult to achieve industrial mass production of thermoset polyphenylene ethers in traditional methods, and the production cost of halogen-free flame retardant high-frequency/high-speed copper clad plate is high.
By introducing unsaturated hydrocarbons containing heteroatoms into the molecular chain of polyarylether resin and reacting with a continuous flow microchannel reactor, the grafting rate and reaction conditions are controlled, a thermoset with excellent dielectric properties and low cost is prepared. polyarylether resin. The resin improves the crosslinkability and flame retardant properties through the esterification reaction of maleic anhydride with hydroxylated unsaturated hydrocarbons, thereby forming a halogen-free flame retardant high-frequency high-speed copper clad plate.
It realizes the low cost and easy industrial production of thermoset polyarylether resin, has excellent dielectric properties and high mechanical strength, can be used in the field of high-frequency and high-speed communications, and has halogen-free flame retardant properties, meeting the requirements of environmental protection laws.
Smart Images

Figure CN119431771A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of communication materials, and in particular relates to a thermosetting polyarylether resin and a prepreg and a halogen-free flame-retardant high-frequency and high-speed copper-clad laminate prepared therefrom. Background Art
[0002] Copper clad laminates are widely used in mobile phones, computers, wearable devices, communication base stations, satellites, driverless cars, drones and intelligent robots, and are one of the key materials in the electronic communications and information industries. Traditional thermosetting resins represented by epoxy resins, phenolic resins and cyanate resins have high thermo-mechanical properties, low thermal expansion coefficients, good quality and low price, easy processing, and strong versatility. They are commonly used materials for making copper clad laminate substrates. After continuous exploration and optimization of formulas and processes, researchers have prepared various types of thermosetting copper clad laminates with qualified comprehensive performance, which meet the basic requirements of copper clad laminates in various segments of the electronic communications industry. However, the dielectric constant and dielectric loss of the above-mentioned traditional thermosetting copper clad laminates are generally very high, which means that they can only be used at low frequencies, and can no longer meet the higher performance requirements for substrate materials in the current high-frequency and high-speed communication fields.
[0003] Later, people developed thermosetting polyphenylene ether-based copper-clad laminates with excellent dielectric properties. At present, thermosetting polyphenylene ether resins can be divided into two categories: end vinyl modified and side vinyl modified. End vinyl modified polyphenylene ether has been commercialized, but its price is extremely expensive, and its cross-linking curing degree is not as good as that of side vinyl modified polyphenylene ether. Side vinyl modified polyphenylene ether has more abundant double bonds and can be self-cured, even without the addition of initiators. Wang Yaoxian et al. first halogenated polyphenylene ether and then used the reaction between halogenated polyphenylene ether and allyl Grignard reagent to prepare thermosetting polyphenylene ether resin with allyl modified side chain (Paper of the 13th National Composite Materials Academic Conference, 2004, 401-405; Chinese Patent CN1563145A; Polymer Bulletin, 2007, 59, 391-402.). However, there is no commercial mass production of allyl Grignard reagents, which often need to be made in the laboratory, and the preparation process is cumbersome, the production cost is high, and it is difficult to store and use. US Patents US3281393, US3422062, US20080194724A1 and Zhang Yufang et al. (Synthesis and Characterization of Cross-linkable Polyphenylene Ether, 2007, Master's Thesis) use phenol derivatives with double bonds such as 2,6-dimethylphenol and 2-allyl-6-methyl-phenol as monomers, potassium ferrocyanide or oxygen as oxidants, and prepare thermosetting polyphenylene ether resins with side allyl groups through oxidative condensation copolymerization. US3281393 further oxidizes the side allyl groups into epoxy functional groups. Similarly, there are no mass-produced products for double-bond phenol monomers represented by 2-allyl-6-methyl-phenol, and the industrial mass production of thermosetting polyphenylene ether cannot be achieved through this copolymerization method. US Patents US3522326, US4923932 and US5218030 use organic metal compounds such as butyl lithium to metallize polyphenylene ether first, and then react with halogenated unsaturated hydrocarbons to graft unsaturated bonds onto the main chain of polyphenylene ether. US3522326 also uses a similar method to modify ethylene oxide onto the polyphenylene ether chain to prepare a thermosetting polyphenylene ether resin that can be cured with epoxy resin. Although organic metal compounds such as butyl lithium have commercial products, they are highly reactive. In traditional kettle reactors, their reactions are highly exothermic, the process is difficult to control, and the risk is high. In addition, it is necessary to ensure that the entire reaction process is always in an inert atmosphere, which places extremely high demands on reaction equipment and process control.
[0004] In addition, due to increasingly stringent environmental laws and policies, the demand for halogen-free flame-retardant high-frequency / high-speed copper clad laminates has also shown a clear upward trend recently. Introducing heteroatoms into the molecular chain of polyarylether resin to improve its flame retardant properties is a good way to achieve halogen-free flame retardancy for high-frequency / high-speed copper clad laminates.
[0005] The continuous flow microchannel reactor is a small reaction system with a pipeline size much smaller than that of a conventional reactor. The miniaturization of the reaction channel can significantly increase the contact area between the channel and the heat exchange medium, improve the heat exchange efficiency, and effectively handle the heat released when polyarylether reacts with organometallic compounds, ensuring that the reaction is orderly, controllable and safe. The extremely strong turbulent process in the microchannel can also increase the mass transfer effect exponentially. At present, the continuous flow microchannel reactor is mainly used in the synthesis of small molecules and their industrial production. There are not many studies and reports on its industrial synthesis and modification of polymers, and most of them are only in the laboratory stage. So far, there has been no research report on the preparation of thermosetting polyarylether using a continuous flow microchannel reactor. In addition, the continuous flow microchannel reactor can realize multi-step continuous reaction, and can be directly scaled up to achieve mass production without pilot testing. It has high safety, controllable production process and high reaction selectivity. Summary of the invention
[0006] The purpose of the present invention is to provide a thermosetting polyarylether resin and a semi-cured sheet and a halogen-free flame-retardant high-frequency and high-speed copper-clad laminate prepared therefrom. In the present invention, the grafting site of the heteroatom-containing unsaturated hydrocarbon can be the Ar-H position or -CH3 on the polyarylether benzene ring; the grafting rate of the heteroatom-containing unsaturated hydrocarbon on the polyarylether molecular chain refers to the proportion of the repeating units grafted with the heteroatom-containing unsaturated hydrocarbon in the polyarylether molecular chain to all the repeating units in the polyarylether molecular chain; the grafting rate can be controlled by the molar ratio of the organometallic compound to the repeating units in the polyarylether molecular chain, or / and the molar ratio of the heteroatom-containing unsaturated hydrocarbon to the organometallic compound. In addition, the carboxyl group produced by the reaction of the heteroatom-containing unsaturated hydrocarbon with maleic anhydride is further esterified with the hydroxylated unsaturated hydrocarbon, and an additional reactive double bond can be introduced into the polyarylether molecular chain, which can improve the cross-linking ability of the thermosetting polyarylether on the one hand, and expand the selectable range of the heteroatom-containing unsaturated hydrocarbon on the other hand, and reduce the cost!
[0007] The present invention further utilizes the uniform dispersion of the composition prepared by the thermosetting polyarylether resin to impregnate fiber cloth and then bake to obtain a prepreg with uniform glue content, strong resin adhesion, flat surface, suitable toughness and viscosity. Finally, the thermosetting copper clad laminate made of the prepreg, film and copper foil has excellent dielectric properties, high mechanical strength, low thermal expansion coefficient, high copper foil peeling strength, good uniformity of various properties, can achieve halogen-free flame retardancy, and can be used to make multi-layer copper clad laminates.
[0008] The present application provides a thermosetting polyarylether resin, characterized in that it comprises a 5.0 wt / v% polyphenylene ether / THF solution, a 0.5 mol / L n-butyl lithium / n-hexane solution, a 1.5 mol / L maleic anhydride / THF solution, methanol, toluene, allyl mercaptan and hydroxypropyl methacrylate.
[0009] The preparation method of the thermosetting polyarylether resin comprises the following steps in sequence:
[0010] S1, respectively passing an organic solution of polyarylether and an organic solution of an organometallic compound into a direct-flow microchannel reactor for preheating through a metering pump; subsequently, the preheated organic solution of polyarylether and the organic solution of an organometallic compound are simultaneously pumped into a reaction module A consisting of N enhanced mixed continuous flow microchannel reactors for reaction; then, the product solution A flowing out of the reaction module A and the organic solution of maleic anhydride are synchronously pumped into a reaction module B consisting of M enhanced mixed continuous flow microchannel reactors for reaction, and then the product solution B flowing out of the reaction module B is added to a poor solvent for polyarylether, stirred evenly, and allowed to stand for the product to be fully precipitated and settled, and then filtered, washed and dried to obtain a polyarylether resin grafted with maleic anhydride;
[0011] S2, after the maleic anhydride grafted polyarylether resin is redissolved in an organic solvent, an unsaturated hydrocarbon containing heteroatoms is added, and the mixture is stirred and reacted at 0-130° C. for 2-96 hours to obtain an organic solution of a carboxylated polyarylether resin containing heteroatoms;
[0012] S3. Add hydroxylated unsaturated hydrocarbon and catalyst to the organic solution of the carboxylated polyarylether resin containing heteroatoms, and stir the mixture at 80-170°C for 12-96h to obtain an organic solution of thermosetting polyarylether resin; then add the mixture to a poor solvent for polyarylether, stir evenly, and let stand to allow the product to fully precipitate and settle, and then filter, wash and dry to obtain a thermosetting polyarylether resin.
[0013] Optionally, the polyarylether in step S1 refers to a mixture of one or more of the polymers having the following chemical structures in the molecular chain:
[0014]
[0015] Wherein, a is between 8 and 400; b≥1, c≥1, and b+c is between 9 and 400; d≥1, e≥1, and d+e is between 9 and 400; f≥0, g≥1, h≥1, i≥1, and g+h+i is between 10 and 400; j≥1, k≥1, l≥1, and j+k+l is between 10 and 400; m≥1, n≥1, o≥1, p≥1, and m+n+o+p is between 11 and 400;
[0016] Wherein, R1 and R2 are one or a combination of the following functional groups:
[0017]
[0018] wherein R3, R4, R5, R6, R7, R8, R9, R10 and R11 each independently represent H and a C1-C12 hydrocarbon chain;
[0019] In addition, one or a mixture of C1-C12 hydrocarbon chains, aromatic groups and their derivatives may be grafted onto the 3rd and 4th positions of the benzene ring in the repeating unit of the polyarylether molecular chain;
[0020] The concentration of the organic solution of polyarylether is 0.01-25wt%; the flux of the organic solution of polyarylether in the direct-flow microchannel reactor is controlled at 1-40mL / min.
[0021] Optionally, the organometallic compound in step S1 is one of alkyl lithium, alkyl sodium and alkyl potassium, or a mixture of several of them; the concentration of the organic solution of the organometallic compound is 0.05-3 mol / L; the solvent in the organic solution of the organometallic compound is one of ether solvents that do not react with the organometallic compound and maleic anhydride, or a mixture of one or several composite solvents of hydrocarbon organic solvents and ditertiary amines, the hydrocarbon organic solvents include cyclohexane, n-hexane, benzene, toluene and xylene, the ditertiary amines include tetramethylethylenediamine, and the ditertiary amines account for 0.2-10wt% of the hydrocarbon organic solvents; the water content of the organic solution of the organometallic compound is ≤0.1wt%, and the oxygen content is ≤0.1v / wt%.
[0022] The molar ratio between the repeating unit and the organometallic compound in the molecular chain of the polyarylether is 1:0.0001-1:2.001;
[0023] The molar ratio between the maleic anhydride and the organometallic compound is 0.01:1-1.01:1.
[0024] Optionally, the direct flow microchannel in step S1 is a channel of a tubular structure, the preheating residence time is set to 5-300s, and the preheating temperature is set to -78°C-150°C; the preheating is controlled by an external heat exchanger, and the heat exchange medium in the external heat exchanger is one of heat transfer oil, water, ice water, ice brine and ethanol;
[0025] The reaction temperature in the reaction modules A and B is also controlled by an external heat exchanger and is consistent with the preheating temperature, the N is between 1-20, the M is between 1-20, the channel in the enhanced hybrid continuous flow microchannel reactor is one of a heart-shaped structure, a water drop-shaped structure, a T-shaped structure, a spherical structure and a spherical structure with baffles, or a combination of several of them, the total reaction time of the polyarylether and the organometallic compound in the reaction module A is 1s-3000s, and the total reaction time of the product solution A and maleic anhydride in the reaction module B is 1s-3000s;
[0026] The hydraulic diameter of the channel in the microchannel reactor is 0.25-10.0 mm, and its material is one of glass, metal and its alloy, ceramic, single crystal silicon, glass with an anti-corrosion layer on the surface, metal and its alloy with an anti-corrosion layer on the surface, ceramic with an anti-corrosion layer on the surface, single crystal silicon with an anti-corrosion layer on the surface, fluorine-containing resin and highly cross-linked thermosetting resin.
[0027] Optionally, the poor solvent for the polyarylene ether in step S1 and step S3 is one or a mixture of methanol, ethanol, isopropanol, butanol, ether and ester.
[0028] Optionally, the unsaturated hydrocarbon containing heteroatoms in step S2 is one or a mixture of substances having the following chemical structures:
[0029]
[0030] Wherein, X1 represents one of -SH, -NH, -NH2, -PH, R12 is not limited, R13, R14 and R15 each independently represent H, methyl and ethyl; the molar ratio of the unsaturated hydrocarbon containing heteroatoms to maleic anhydride is controlled in the range of 0.1:1-1.001:1;
[0031] Compounds containing active hydrogen and S, N, P, etc. that can react with maleic anhydride, even if they do not contain reactive double bonds, can also be used to replace the unsaturated hydrocarbon containing heteroatoms described in step S2;
[0032] The hydroxylated unsaturated hydrocarbon is one or a mixture of substances having the following chemical structures:
[0033] Wherein, X2 and X3 each independently represent a hydroxyl group, R16 and R20 are not limited, R17, R18, R19 and R21 each independently represent H, methyl and ethyl; the molar ratio of the hydroxylated unsaturated hydrocarbon to the heteroatom-containing unsaturated hydrocarbon is controlled at 0.98:1-1.5:1.
[0034] The catalyst is not particularly limited, and any compound can be used as long as it can catalyze the esterification reaction between hydroxyl and carboxyl groups.
[0035] A prepreg made of a thermosetting polyarylether resin, the preparation method comprising: preparing an organic solution of the thermosetting polyarylether resin, adding a polydiene resin, a crosslinking agent and an initiator, stirring evenly to obtain a uniform dispersion of a thermosetting polyarylether resin-based composition, wherein the solid content of the dispersion is controlled to be 20-80 wt / v%; then impregnating a fiber cloth with the uniform dispersion of the thermosetting polyarylether resin-based composition, and baking and drying to obtain the prepreg.
[0036] A copper-clad laminate prepared from a prepreg, the preparation method comprising: laminating the prepreg and the copper foil covering the surface together, and preparing the halogen-free flame-retardant high-frequency and high-speed copper-clad laminate through a lamination process.
[0037] Optionally, the number average molecular weight of the polydiene resin is between 500 and 20,000, and the side groups of a single polydiene polymer chain contain at least 3 reactive carbon-carbon double bonds in total;
[0038] The crosslinking agent is one or a mixture of TAIC (triallyl isocyanurate), TAC (triallyl cyanurate), divinylbenzene, trimethylolpropane trimethacrylate, bismaleimide and derivatives thereof, and its amount accounts for 0-30.0wt% of the thermosetting polyarylether resin-based composition;
[0039] The initiator is one or a mixture of free radical initiators such as peroxide, azo compound and redox system that can be dissolved in a solvent that makes the thermosetting polyarylether resin-based composition uniformly dispersed, and its amount accounts for 0.01-5wt% of the thermosetting polyarylether resin-based composition;
[0040] The solvent of the uniform dispersion is one of water and an organic solvent, or a mixture of several solvents that can disperse the thermosetting polyarylether resin-based composition;
[0041] When the polydiene resin, crosslinking agent and initiator are added, fillers, flame retardants, compatibilizers, toughening agents and modified resins may also be added.
[0042] Optionally, the copper clad laminate further includes a film, which is a mixture of one or more of fluoropolymers, polyimides, polyolefins, polyaromatic hydrocarbons, polyamides, polyether ketones, polyether ether ketones, polyarylethers, polyarylether sulfides, polyarylether sulfones, polyarylether sulfones, polyarylether ketones, polyarylether sulfide ketones, polyether sulfone ketones, polyarylether sulfone nitrile, polyarylether sulfone nitrile, polyphenylquinoxaline, phenolic resins, epoxy resins, cyanate resins, polyesters, polycarbonates, polyurethanes and polyoxymethylene and their derivatives.
[0043] Compared with the prior art, the technical solution of this application has the following beneficial effects:
[0044] The invention has mild preparation conditions, low production cost, is easy to mass-produce and scale production, has strong universality, and has a good industrial production foundation and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0046] Figure 1 The present invention provides a thermosetting polyarylether resin, a prepreg prepared therefrom, and a halogen-free flame-retardant high-frequency and high-speed copper-clad laminate according to embodiments 1 to 6. DETAILED DESCRIPTION
[0047] Synthesis example 1
[0048] A 5.0 wt / v% polyphenylene ether / THF solution and a 0.5 mol / L n-butyl lithium / n-hexane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.07; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The heating temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added to control the molar ratio of allyl mercaptan to maleic anhydride to be 1:1, and after stirring and reacting at 60°C for 48h, an allyl mercaptan grafted carboxylated polyarylether resin / toluene solution is obtained. The 1H-NMR test shows that the grafting rate of allyl mercaptan is 4.15wt%.
[0049] Then, hydroxypropyl methacrylate is added to the toluene solution of the carboxylated polyphenylene ether grafted with allyl mercaptan, and the molar number of hydroxypropyl methacrylate is 1.2 times that of allyl mercaptan; under the catalysis of concentrated sulfuric acid, after condensation reflux and toluene with water, the esterification product, i.e., thermosetting polyarylether resin / toluene solution, is obtained after 16 hours of reaction. Finally, excess methanol is added to allow the polymer to be fully precipitated and precipitated, and then filtered, washed with methanol and dried to obtain a thermosetting polyphenylene ether resin.
[0050] Synthesis example 2
[0051] A 5.0 wt / v% polyphenylene ether / THF solution and a 0.5 mol / L n-butyl lithium / n-hexane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.12; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to 5°C and the reaction residence time was 200 s. The temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added to control the molar ratio of allyl mercaptan to maleic anhydride to be 1:1, and after stirring and reacting at 60°C for 48h, an allyl mercaptan grafted carboxylated thermosetting polyarylether resin / toluene solution is obtained. The 1H-NMR test shows that the side vinyl grafting rate of allyl mercaptan is 9.23wt%.
[0052] Then, hydroxypropyl methacrylate is added to the toluene solution of the carboxylated polyphenylene ether grafted with allyl mercaptan, and the molar number of hydroxypropyl methacrylate is 1.2 times that of allyl mercaptan; under the catalysis of concentrated sulfuric acid, after condensation reflux and toluene with water, the esterification product, i.e., thermosetting polyarylether resin / toluene solution, is obtained after 16 hours of reaction. Finally, excess methanol is added to allow the polymer to be fully precipitated and precipitated, and then filtered, washed with methanol and dried to obtain a thermosetting polyphenylene ether resin.
[0053] The thermosetting polyphenylene ether resin collected in Synthesis Example 2 was redissolved in toluene, and 0.5 wt% dicumyl peroxide was added. After stirring evenly, the solution was placed in a 45°C blowing oven for heat treatment to fully evaporate the solvent to obtain a polymer film; finally, the polymer film was placed in a 180°C oven for heat treatment for 30 minutes to obtain a cross-linked polyphenylene ether film. Even when toluene was heated, the cross-linked polyphenylene ether film could no longer be dissolved in toluene.
[0054] Synthesis example 3
[0055] A 5.0 wt / v% polyphenylene ether / THF solution and a 1.2 mol / L tert-butyl lithium / n-pentane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.28; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to The temperature of the reaction module A is 5°C, and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added to control the molar ratio of allyl mercaptan to maleic anhydride to be 0.51:1, and after stirring and reacting at 60°C for 48h, an allyl mercaptan grafted carboxylated thermosetting polyarylether resin / toluene solution is obtained. The 1H-NMR test shows that the grafting rate of allyl mercaptan is 12.1wt%.
[0056] Then, hydroxyethyl methacrylate is added to the toluene solution of the carboxylated polyphenylene ether grafted with allyl mercaptan, and the molar number of hydroxyethyl methacrylate is 1.15 times that of allyl mercaptan; under the catalysis of p-toluenesulfonic acid, after condensation reflux and toluene with water, the esterification product, i.e., thermosetting polyarylether resin / toluene solution, is obtained after 14 hours of reaction. Finally, excess methanol is added to allow the polymer to be fully precipitated and precipitated, and then filtered, washed with methanol and dried to obtain a thermosetting polyphenylene ether resin.
[0057] Synthesis example 4
[0058] A 5.0 wt / v% polyphenylene ether / THF solution and a 1.6 mol / L tert-butyl lithium / n-pentane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.38; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to The temperature of the reaction module A is 5°C, and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added to control the molar ratio of allyl mercaptan to maleic anhydride to be 0.95:1, and after stirring and reacting at 60°C for 72h, an allyl mercaptan grafted carboxylated thermosetting polyarylether resin / toluene solution is obtained. The 1H-NMR test shows that the grafting rate of allyl mercaptan is 28.1wt%.
[0059] Then, hydroxyethyl methacrylate is added to the toluene solution of the carboxylated polyphenylene ether grafted with allyl mercaptan, and the molar number of hydroxyethyl methacrylate is 1.15 times that of allyl mercaptan; under the catalysis of p-toluenesulfonic acid, after condensation reflux and toluene with water, the esterification product, i.e., thermosetting polyarylether resin / toluene solution, is obtained after 16 hours of reaction. Finally, excess methanol is added to allow the polymer to be fully precipitated and precipitated, and then filtered, washed with methanol and dried to obtain a thermosetting polyphenylene ether resin.
[0060] Synthesis example 5
[0061] A 5.0 wt / v% polyphenylene ether / THF solution and a 1.6 mol / L tert-butyl lithium / n-pentane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.35; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to The temperature of the reaction module A is 5°C, and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added to control the molar ratio of allyl mercaptan to maleic anhydride to be 0.85:1, and after stirring and reacting at 60°C for 72h, an allyl mercaptan grafted carboxylated thermosetting polyarylether resin / toluene solution is obtained. The 1H-NMR test shows that the grafting rate of allyl mercaptan is 23.3wt%.
[0062] Then, hydroxyethyl methacrylate is added to the toluene solution of the carboxylated polyphenylene ether grafted with allyl mercaptan, and the molar number of hydroxyethyl methacrylate is 1.15 times that of allyl mercaptan; under the catalysis of concentrated sulfuric acid, after condensation reflux and toluene with water, the esterification product, i.e., thermosetting polyarylether resin / toluene solution, is obtained after 16 hours of reaction. Finally, excess methanol is added to allow the polymer to be fully precipitated and precipitated, and then filtered, washed with methanol and dried to obtain a thermosetting polyphenylene ether resin.
[0063] Synthesis example 6
[0064] A 5.0 wt / v% polyphenylene ether / THF solution and a 1.2 mol / L tert-butyl lithium / n-pentane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.26; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to The temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 0.98:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and DOPO is added to control the molar ratio of DOPO to maleic anhydride to be 1:1, and after stirring and reacting at 80°C for 72h, a DOPO-grafted carboxylated thermosetting polyarylether resin / toluene solution is obtained. The 1H-NMR and 31P-NMR tests show that the grafting rate of DOPO is 15.8wt%.
[0065] Then, hydroxyethyl methacrylate is added to the toluene solution of the DOPO-grafted carboxylated polyphenylene ether, and the molar number of hydroxyethyl methacrylate is 1.25 times that of allyl mercaptan; under the catalysis of p-toluenesulfonic acid, after condensation reflux and toluene with water, the esterification product, namely the thermosetting polyarylether resin / toluene solution, is obtained after 18 hours of reaction. Finally, excess methanol is added to allow the polymer to be fully precipitated and precipitated, and then filtered, washed with methanol and dried to obtain the thermosetting polyphenylene ether resin.
[0066] Example 1
[0067] Take 100 parts of the thermosetting polyarylether resin in Synthesis Example 1, 35 parts of polybutadiene (Crayville Ri con154), 5 parts of bismaleimide resin, 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ri con130MA8), 50 parts of silicon oxide, 200 parts of boehmite, 10 parts of aluminum oxide, 50 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50°C for 24 hours, fully dissolve and disperse evenly; cool to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5min, and the second stage baking temperature is 120°C, the time is 2min; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0068] Example 2
[0069] Take 100 parts of the thermosetting polyarylether resin in Synthesis Example 2, 30 parts of polybutadiene (Crayville Ri con154), 5 parts of bismaleimide resin, 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ri con130MA8), 100 parts of silicon oxide, 150 parts of boehmite, 10 parts of aluminum oxide, 40 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50°C for 24 hours, fully dissolve and disperse evenly; cool to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5min, and the second stage baking temperature is 120°C, the time is 2min; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0070] Example 3
[0071] Take 100 parts of the thermosetting polyarylether resin in Synthesis Example 3, 5 parts of bismaleimide resin, 30 parts of polybutadiene (Crayville Ricon 154), 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ricon 130MA8), 120 parts of silicon oxide, 130 parts of boehmite, 10 parts of aluminum oxide, 35 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50°C for 24 hours, fully dissolve and disperse evenly; cool to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5min, and the second stage baking temperature is 120°C, the time is 2min; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0072] Example 4
[0073] Take 100 parts of the thermosetting polyarylether resin in Synthesis Example 4, 28 parts of polybutadiene (Crayville Ri con154), 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ri con130MA8), 150 parts of silicon oxide, 100 parts of boehmite, 10 parts of aluminum oxide, 35 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50°C for 24 hours, fully dissolve and disperse evenly; cool to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5min, and the second stage baking temperature is 120°C, the time is 2min; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0074] Example 5
[0075] Take 100 parts of the thermosetting polyarylether resin in Synthesis Example 5, 25 parts of polybutadiene (Crayville Ri con154), 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ri con130MA8), 150 parts of silicon oxide, 100 parts of boehmite, 10 parts of aluminum oxide, 30 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50°C for 24 hours, fully dissolve and disperse evenly; cool to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5min, and the second stage baking temperature is 120°C, the time is 2min; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0076] Example 6
[0077] Take 100 parts of the thermosetting polyarylether resin in Synthesis Example 6, 20 parts of polybutadiene (Crayville Ri con154), 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ri con130MA8), 175 parts of silicon oxide, 75 parts of boehmite, 10 parts of aluminum oxide, 30 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50°C for 24 hours, fully dissolve and disperse evenly; cool to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5min, and the second stage baking temperature is 120°C, the time is 2min; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
Claims
1. A thermosetting polyarylether resin, characterized in that: The invention comprises a 5.0 wt / v% polyphenylene ether / THF solution, a 0.5 mol / L n-butyl lithium / n-hexane solution, a 1.5 mol / L maleic anhydride / THF solution, methanol, toluene, allyl mercaptan and hydroxypropyl methacrylate, The preparation method of the thermosetting polyarylether resin comprises the following steps in sequence: S1, respectively passing an organic solution of polyarylether and an organic solution of an organometallic compound into a direct-flow microchannel reactor for preheating through a metering pump; subsequently, the preheated organic solution of polyarylether and the organic solution of an organometallic compound are simultaneously pumped into a reaction module A consisting of N enhanced mixed continuous flow microchannel reactors for reaction; then, the product solution A flowing out of the reaction module A and the organic solution of maleic anhydride are synchronously pumped into a reaction module B consisting of M enhanced mixed continuous flow microchannel reactors for reaction, and then the product solution B flowing out of the reaction module B is added to a poor solvent for polyarylether, stirred evenly, and allowed to stand for the product to be fully precipitated and settled, and then filtered, washed and dried to obtain a polyarylether resin grafted with maleic anhydride; S2, after the maleic anhydride grafted polyarylether resin is redissolved in an organic solvent, an unsaturated hydrocarbon containing heteroatoms is added, and the mixture is stirred and reacted at 0-130° C. for 2-96 hours to obtain an organic solution of a carboxylated polyarylether resin containing heteroatoms; S3. Add hydroxylated unsaturated hydrocarbon and catalyst to the organic solution of the carboxylated polyarylether resin containing heteroatoms, and stir the mixture at 80-170°C for 12-96h to obtain an organic solution of thermosetting polyarylether resin; then add the mixture to a poor solvent for polyarylether, stir evenly, and let stand to allow the product to fully precipitate and settle, and then filter, wash and dry to obtain a thermosetting polyarylether resin.
2. A thermosetting polyarylether resin according to claim 1, characterized in that: The polyarylether in step S1 refers to a mixture of one or more of the polymers having the following chemical structures in the molecular chain: Wherein, a is between 8 and 400; b≥1, c≥1, and b+c is between 9 and 400; d≥1, e≥1, and d+e is between 9 and 400; f≥0, g≥1, h≥1, i≥1, and g+h+i is between 10 and 400; j≥1, k≥1, l≥1, and j+k+l is between 10 and 400; m≥1, n≥1, o≥1, p≥1, and m+n+o+p is between 11 and 400; Wherein, R1 and R2 are one or a combination of the following functional groups: wherein R3, R4, R5, R6, R7, R8, R9, R10 and R11 each independently represent H and a C1-C12 hydrocarbon chain; In addition, one or a mixture of C1-C12 hydrocarbon chains, aromatic groups and their derivatives may be grafted onto the 3rd and 4th positions of the benzene ring in the repeating unit of the polyarylether molecular chain; The concentration of the organic solution of polyarylether is 0.01-25wt%; the flux of the organic solution of polyarylether in the direct-flow microchannel reactor is controlled at 1-40mL / min.
3. The method for preparing a thermosetting polyarylether resin according to claim 1, characterized in that: The organometallic compound in step S1 is one of alkyl lithium, alkyl sodium and alkyl potassium, or a mixture of several thereof; the concentration of the organic solution of the organometallic compound is 0.05-3 mol / L; the solvent in the organic solution of the organometallic compound is one of ether solvents that do not react with the organometallic compound and maleic anhydride, or a mixture of one or several composite solvents of hydrocarbon organic solvents and di-tertiary amines, the hydrocarbon organic solvents include cyclohexane, n-hexane, benzene, toluene and xylene, the di-tertiary amines include tetramethylethylenediamine, and the di-tertiary amines account for 0.2-10 wt% of the hydrocarbon organic solvents; the water content of the organic solution of the organometallic compound is ≤0.1 wt%, and the oxygen content is ≤0.1 v / wt%. The molar ratio between the repeating unit and the organometallic compound in the molecular chain of the polyarylether is 1:0.0001-1:2.001; The molar ratio between the maleic anhydride and the organometallic compound is 0.01:1-1.01:
1.
4. The thermosetting polyarylether resin according to claim 1, characterized in that: The direct-flow microchannel in step S1 is a channel of tubular structure, and the preheating residence time is set to 5-300s, and the preheating temperature is set to -78°C-150°C; the preheating is controlled by an external heat exchanger, and the heat exchange medium in the external heat exchanger is one of heat transfer oil, water, ice water, ice salt water and ethanol; The reaction temperature in the reaction modules A and B is also controlled by an external heat exchanger and is consistent with the preheating temperature, the N is between 1-20, the M is between 1-20, the channel in the enhanced hybrid continuous flow microchannel reactor is one of a heart-shaped structure, a water drop-shaped structure, a T-shaped structure, a spherical structure and a spherical structure with baffles, or a combination of several of them, the total reaction time of the polyarylether and the organometallic compound in the reaction module A is 1s-3000s, and the total reaction time of the product solution A and maleic anhydride in the reaction module B is 1s-3000s; The hydraulic diameter of the channel in the microchannel reactor is 0.25-10.0 mm, and its material is one of glass, metal and its alloy, ceramic, single crystal silicon, glass with an anti-corrosion layer on the surface, metal and its alloy with an anti-corrosion layer on the surface, ceramic with an anti-corrosion layer on the surface, single crystal silicon with an anti-corrosion layer on the surface, fluorine-containing resin and highly cross-linked thermosetting resin.
5. The thermosetting polyarylether resin according to claim 1, characterized in that: The poor solvent of the polyarylether in step S1 and step S3 is one or a mixture of methanol, ethanol, isopropanol, butanol, ether and ester.
6. The thermosetting polyarylether resin according to claim 1, characterized in that: The unsaturated hydrocarbon containing heteroatoms in step S2 is one or a mixture of substances having the following chemical structures: Wherein, X1 represents one of -SH, -NH, -NH2, -PH, R12 is not limited, R13, R14 and R15 each independently represent H, methyl and ethyl; the molar ratio of the unsaturated hydrocarbon containing heteroatoms to maleic anhydride is controlled in the range of 0.1:1-1.001:1; Compounds containing active hydrogen and S, N, P, etc. that can react with maleic anhydride, even if they do not contain reactive double bonds, can also be used to replace the unsaturated hydrocarbon containing heteroatoms described in step S2; The hydroxylated unsaturated hydrocarbon is one or a mixture of substances having the following chemical structures: Wherein, X2 and X3 each independently represent a hydroxyl group, R16 and R20 are not limited, R17, R18, R19 and R21 each independently represent H, methyl and ethyl; the molar ratio of the hydroxylated unsaturated hydrocarbon to the heteroatom-containing unsaturated hydrocarbon is controlled at 0.98:1-1.5:
1. The catalyst is not particularly limited, and any compound can be used as long as it can catalyze the esterification reaction between hydroxyl and carboxyl groups.
7. A prepreg prepared from the thermosetting polyarylether resin as claimed in claim 1, characterized in that The preparation method comprises the following steps: preparing an organic solution of the thermosetting polyarylether resin, adding a polydiene resin, a crosslinking agent and an initiator, stirring evenly to obtain a uniform dispersion of a thermosetting polyarylether resin-based composition, and controlling the solid content thereof to be 20-80 wt / v%; then impregnating a fiber cloth with the uniform dispersion of the thermosetting polyarylether resin-based composition, and baking and drying the fiber cloth to obtain the semi-cured sheet.
8. A copper-clad laminate prepared from the prepreg according to claim 7, characterized in that The preparation method is: stacking the prepreg and the copper foil covering the surface together, and preparing the halogen-free flame-retardant high-frequency and high-speed copper-clad laminate through a lamination process.
9. The prepreg prepared from a thermosetting polyarylether resin according to claim 7, characterized in that: The number average molecular weight of the polydiene resin is between 500 and 20,000, and the side groups of a single polydiene polymer chain contain at least three reactive carbon-carbon double bonds in total; The crosslinking agent is one or a mixture of TAIC (triallyl isocyanurate), TAC (triallyl cyanurate), divinylbenzene, trimethylolpropane trimethacrylate, bismaleimide and derivatives thereof, and its amount accounts for 0-30.0wt% of the thermosetting polyarylether resin-based composition; The initiator is one or a mixture of free radical initiators such as peroxide, azo compound and redox system that can be dissolved in a solvent that makes the thermosetting polyarylether resin-based composition uniformly dispersed, and its amount accounts for 0.01-5wt% of the thermosetting polyarylether resin-based composition; The solvent of the uniform dispersion is one of water and an organic solvent, or a mixture of several solvents that can disperse the thermosetting polyarylether resin-based composition; When the polydiene resin, crosslinking agent and initiator are added, fillers, flame retardants, compatibilizers, toughening agents and modified resins may also be added.
10. The copper-clad laminate prepared from a prepreg according to claim 8, characterized in that: The copper clad laminate also includes a film, which is a mixture of one or more of fluorine-containing polymers, polyimides, polyolefins, polyaromatic hydrocarbons, polyamides, polyether ketones, polyether ether ketones, polyarylethers, polyarylether sulfides, polyarylether sulfones, polyarylether sulfones, polyarylether ketones, polyarylether sulfide ketones, polyether sulfone ketones, polyarylether sulfone nitrile, polyarylether sulfone nitrile, polyphenylquinoxaline, phenolic resins, epoxy resins, cyanate resins, polyesters, polycarbonates, polyurethanes, polyoxymethylenes and their derivatives.
Citation Information
Patent Citations
Preparing thermosetting phlyphenylether through Geliya reagent in polyphenylether halide and allyl group type
CN1563145A
Method of forming a crosslinked poly(arylene ether) film, and film formed thereby
US20080194724A1
Phenylene oxide polymers substituted with epoxidized alkenyl groups
US3281393A
Copolymers of alkenyl phenol
US3422062A
Graft copolymers of polyphenylene ethers
US3522326A